HOTAIR: A Promising Long Non-coding RNA with Potential Role in Breast Invasive Carcinoma - Avazpour, Niloofar; Hajjari, Mohammadreza; Tahmasebi Birgani, Maryam (Frontiers in Genetics, 2017)
Long non-coding RNAs have different molecular and cellular function. Emerging role of lncRNA as regulatory factors indicate that dysregulation of these transcripts can be involved in variety of diseases such as cancers. HOTAIR is one of the most cited lncRNAs with an oncogenic role in different human malignancies such as breast cancer. So, it could be considered as a potential biomarker in different cancers specially breast tumors. However, the association of this RNA with different features of breast invasive carcinoma is poorly understood. Here, we describe a comprehensive analysis of HO-TAIR alteration in a large cohort of breast tissues and present its association with differ-ent features of breast cancer based on a large cohort of tumor tissues derived from TCGA data. This provides a resource for investigating the HOTAIR in breast invasive carcinoma and lays the basis for the development of new studies considering this lncRNA as a potential biomarker and therapeutic target.